Faktor-Faktor Yang Mempengaruhi Tax Avoidance Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Monicha Lorenza (Jurnal Literasi Akuntansi, 2022)
This study aims to examine Return On Assets, Leverage, Size, Tax Loss Carryforwards, Institutional Ownership and The Risk Companies to Tax avoidance. The sample used in this study is the basic and chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Sampling using purposive sampling method and obtained 15 companies with data processed 80 annual financial statements. This research technique uses multiple linear regression analysis with SPSS 20 test equipment. The results of this study indicate that leverage, institutional ownership and company risk positive affect tax avoidance. Meanwhile, ROA, size, tax loss carryforwards loss have no effect on tax avoidance.